A Rare Case of Methionine Adenosyltransferase Deficiency in an 8-Month-Old Infant Presenting with Jaundice and Bleeding Episodes (Global Journal of Medical Research, 2023)
Methionine adenosyltransferase MAT deficiency is a rare inherited disorder of methionine metabolism that can lead to a wide range of symptoms including jaundice bleeding episodes and neurological impairment We report the case of an 8-month-old female infant who presented with yellowish discoloration of skin distended abdomen and bleeding episodes On further evaluation she was found to have high levels of methionine in her blood A diagnosis of MAT deficiency was made and was started on appropriate treatment with a methioninerestricted diet and supplements